A mediação pedagógica do professor na brincadeira da criança com autismo - Salles, Flaviane Lopes Siqueira (2018)
The aim of this study is to understand the pedagogical mediation methods developed by the teacher to better address the challenges of including, guiding and contributing to the self - regulation of children 's activities in play activities in the context of a university library. Faced with this challenge, a case study was carried out in a university playroom and other play spaces used as an extension of it, having as subjects a teacher / toyist and one of the children diagnosed with autism for observation, follow-up, analysis and discussion of the mediator action of the teacher / toyist with her. The historical-cultural perspective constituted the theoretical and methodological basis of this study, sharing the theoretical reference of Vygotsky (1983, 1997) and other authors who consider the development of subjects from the relationships and interactions that are made possible in the mediated processes. For data collection, we used filming, semi-structured interview with the parents and / or those responsible for children with autism and participant observation. The data were analyzed through the use of content analysis and microgenetic analysis. The results indicate the relevance of the identification throughout the teaching and learning process, of two movements made by the mediating action of the teacher with the child that marked important qualitative leaps in this relation, namely: a) adaptation movement: understanding the modes of being and being of the child with autism in the toy library; b) approximation movement: increasing the participation of the child with autism in the context of the game. The pedagogical mediations developed by the teacher guided the child's actions with autism to what was possible in certain situations, respecting their particularities. In the adaptation movement, in general terms, they configured important educational actions: the individualized monitoring by the teacher / toyist, accepting and placing as reference in the process of teaching and learning of the child with autism in the course of the work with the class; the use of an individualized education plan (PEI); respect for the individuality and characteristics of the child; collective and collaborative work; the involvement and involvement of the family; and the discovery and performance in areas of interest to the child with autism. In the movement of approximation, in general lines, they configured important educational actions: the process of sensitization of the children of the Center for Early Childhood Education to the issue of difference / diversity, through the art of storytelling, using stories from children's literature; the organization in small groups and the expansion of the child's experiences in play, in the physical and social environment and in the relationship with the other, through movements that varied from the individual to the collective and from the collective to the individual. Finally, our reflections point out that, due to the sensitivity of re-signifying times / spaces according to the singularities of each child and in collaborative work, pedagogical mediation can favor the development of children with autism, allowing them to broaden their relationship with the environment.